Invasive ductal breast carcinoma with predominant intraductal component: Clinicopathological features and prognosis. (June 2016) - Sabatier, Renaud; Sabiani, Laura; Zemmour, Christophe; Taix, Sébastien; Chereau, Elisabeth; Gonçalves, Anthony; Jalaguier-Coudray, Aurélie; Charafe-Jauffret, Emmanuelle; Resbeut, Michel; Extra, Jean-Marc; Viens, Patrice; Tallet, Agnès
Abstract: Purpose: Invasive ductal carcinoma with predominant intraductal component (IDCPIC) represents almost 5% of breast cancers. Nevertheless few data exist concerning their characteristics and prognostic behaviour. Our objective was to describe IDCPIC's clinicopathological and prognostic features and compare them to that of invasive ductal carcinoma without predominant intraductal component (IDC). Methods: Retrospective single centre study including all the localized invasive ductal carcinoma listed in our institutional database. Clinical, radiological and pathological criteria were collected as well as disease-free survival (DFS) data. Results: From 1995 to 2008, 4109 invasive ductal breast cancers treated were included. Out of them 192 (4.7%) were IDCPIC. Most of IDCPIC (63%) were discovered by radiological screening whereas IDC suspicion was more often clinical (82.7% vs 49.5%, p < 0.001). Pathological lymph node involvement was less frequent in IDCPIC (35.8 vs 44.3%, p = 0.04). Invasive tumour median size was 2-fold smaller in IDCPIC (10 mm vs 20 mm, p< 0.001). Hormone receptors expression was similar between both groups whereas HER2 overexpression was more frequent in IDCPIC (32% vs 14.3%, p< 0.001). Mastectomy was more frequently performed for IDCPIC (67.7% vs 30.3%, p < 0.001) whereas chemotherapy and radiation therapy were less frequent (55.5% vs 68%, and 82.8% vs 95.5%, respectively, p < 0.001 for both). After matching for discriminant clinicopathological features (tumour size, lymph node involvement, vascular invasion, HER2), DFS was similar in both groups (5-year DFS of 87.4% vs 84.4%, p = 0.47). Conclusion: IDCPIC and other IDC with invasive components showing similar clinicopathological features display a similar prognosis. Highlights: Invasive Ductal Carcinoma with Predominant Intraductal Component represents 5% of breast cancers. We show here the first study on IDCPIC for Caucasian patients. IDCPIC and other invasive ductal carcinoma display similar clinicopathological features. Prognosis depends on clinicopathological features of the invasive component.